2001
DOI: 10.1006/qres.2001.2259
|View full text |Cite
|
Sign up to set email alerts
|

Paleoclimatic Reconstruction Using the Correlation in δ18O of Hackberry Carbonate and Environmental Water, North America

Abstract: Celtis sp. (commonly known as “hackberry”) fruits were collected from 101 North American sites located in 13 states and one Canadian province between the years of 1979–1994. The biomineralized carbonate endocarp of the hackberry, which is a common botanical fossil found throughout the Quaternary sediments of the Great Plains, was analyzed for its δ18O value and plotted against the δ18O value of site environmental water to demonstrate the potential of the hackberry as a paleoclimate indicator. This correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
41
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(60 citation statements)
references
References 30 publications
16
41
2
Order By: Relevance
“…These fruits do not even need to have been in contact with fire to be preserved as the carbonated composition and sometimes silica bodies contained in their fruit stones contribute to their mineralisation (Retallack, 1990;Jahren et al, 1998Jahren et al, , 2001Pustovoytov and Riehl, 2006). Due to this phenomenon, it is possible to identify different genera in a precise manner and thus to reconstruct environmental conditions even in Early Pleistocene times.…”
Section: Discussionmentioning
confidence: 99%
“…These fruits do not even need to have been in contact with fire to be preserved as the carbonated composition and sometimes silica bodies contained in their fruit stones contribute to their mineralisation (Retallack, 1990;Jahren et al, 1998Jahren et al, , 2001Pustovoytov and Riehl, 2006). Due to this phenomenon, it is possible to identify different genera in a precise manner and thus to reconstruct environmental conditions even in Early Pleistocene times.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that most fossil plants harvested for their hackberries at Aşıklı are drawing on evaporated soil water, rather than the local (perched and regional) water table sampled in our study. We compare these analyses to that of endocarps predicted to form from a range of local meteoric waters (horizontal lines) using the endocarp-water relationship for North American hackberries described in Jahren et al (2001) (see text). An interesting exception is represented by four endocarps, samples AH-64a-d in Table 3.…”
Section: Stable Isotopic Compositionmentioning
confidence: 99%
“…Boraginaceae) and its potential for paleoclimate research. Previously, biogenic carbonate in fruits of flowering plants has been studied isotopically in the genus Celtis (Wang et al, 1997;Jahren et al, 1998Jahren et al, , 2001. These works addressed the processes of biomineralization in fruit tissues (Jahren et al, 1998) as well as the radiocarbon content (Wang et al, 1997) and oxygen isotopic composition (Jahren et al 2001) of fruit carbonate.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, biogenic carbonate in fruits of flowering plants has been studied isotopically in the genus Celtis (Wang et al, 1997;Jahren et al, 1998Jahren et al, , 2001. These works addressed the processes of biomineralization in fruit tissues (Jahren et al, 1998) as well as the radiocarbon content (Wang et al, 1997) and oxygen isotopic composition (Jahren et al 2001) of fruit carbonate. It has been demonstrated that the δ 18 O values of biogenic carbonate in Celtis fruits are correlated to δ 18 O of local meteoric water and, for the studied ecological range, also to mean annual temperatures (Jahren et al, 2001).…”
Section: Introductionmentioning
confidence: 99%